STRATEGI PENGEMBANGAN PEMANTAUAN KUOTA PENANGKAPAN IKAN UNTUK SUATU WILAYAH PENGELOLAAN PERIKANAN DI INDONESIA - Muhammad Fedi Alfiadi Sondita; Nida Mardhiyah Ramdhani; Tri Wiji Nurani (Bogor Agricultural University, 2022)
Catch quota would be less effective to control fishing activities if fish production is not monitored properly. Limited support and participation of business players in fish monitoring program are contributing factors to the unreliability of fisheries statistics in many places, including Indonesia. To address this challenge, Indonesia fisheries managers may consider experiences of some fisheries management bodies with advanced monitoring system. This study analyzed the process of establishment of a monitoring system developed by Commission for the Conservation of Southern Bluefin Tuna (CCSBT) to direct each affiliated country to monitor its catch quota. The study was conducted in June-November 2020 by conducting interviews and literature review. CCSBT implements a monitoring system called the catch documentation scheme (CDS) to record the captured/cultured/traded southern bluefin tuna (SBT). Its development started from discussions to solve data insufficiency for SBT stock assessment. These discussions promoted engagement of its affiliated countries, business players and fisheries experts. CCSBT is successful in building the capacity of some affiliate countries which implement the CDS under supervision of CCSBT. Such process was effective in building compliance of business players in the affiliate countries. In preparation of new fisheries management regime, Ministry of Marine Affairs and Fisheries may consider adapting this process by positioning CCSBT as a Fisheries Management Authority and affiliate members as provincial fisheries management bodies. Based on the CCSBT's experience, advocacy in public awareness on fisheries crisis and provision of preliminary data are two priority strategies in bringing stakeholders to build an effective fish monitoring program.